The effectivity of Annona squamosa L seeds extracted by diverse organic solvents: water, methanol and hexane against mortality of tick larvae, Boophilus microplus in vitro - Wardhana, April H; Husein, Amir; Manurung, J (Indonesian Animal Sciences Society, 2005)
Boophilus microplus is the most important pest in livestock industries. The use of synthetic chemical acaricides is the main method of tick control, however, chemical acaricides are expensive, and they are harmful to environment and cause strain resistance. The aim of study was to investigate the affectivity of Annona squamosa L seeds extracted by diverse organic solvents such as water, methanol and hexane against mortality of Boophilus microplus larvae in vitro. Five hundred and fifty larvae were used in this study and divided into three groups e.g. water (3, 4 and 5% concentration), methanol and hexane extract groups (0.25, 0.50, and 0.75% concentration). Coumaphos (0.50%) was used as a positive control. The larvae were dipped into extract solution for 10 seconds and dried using filter paper. Their mortality was observed from one to five hours. The mortality data were transformed to Abbot formula and analyzed using probit analysis with 95% significant level. This study showed that the active compound of Annona squamosa L seeds had effectively contact toxic property for B. microplus larvae at 5, 0.50, and 0.75% for water, methanol and hexane extractions, respectively. The lethal concentrations of methanol extract (LC50, LC90, and LC95) were lower than hexane extract e.g. 0.32, 0.86, and 1.13%, respectively and for hexane extract were 0.35, 1.11, and 1.54%, respectively at fifth hour. The lethal times of methanol extract on 0.50% concentration were shorter than hexane extract e.g. 3.12 hours (LT50), 5.86 hours (LT90), and 7.00 hours (LT95) and for hexane extract on 0.75% concentration were 3.26 hours (LT50), 6.21 hours (LT90), and 7.45 hours (LT95). Water extract of 5% concentration was effective for traditional farmer in rural area due to easy and cheap method. The lethal concentrations of water extract on fifth hour were 2.02% (LC50), 4.00% (LC90), and 4.85% (LC95) and the lethal time on 5% concentration were 2.54 hours (LT50), 4.13 hours (LT90), and 4.75 hours (LT95). Â Â Key Words: Annona squamosa, Boophilus microplus, Water Extract, Methanol, Hexane